On difference between international crimes stristo sensu and lato sensu - Krivokapić Boris (Strani pravni život, 2018)
The article deals with the problem of dividing international criminal into those in the wider and broader sense. The first part points to the essence of this division and the fact that it appeared at the XIV International Association of Penal Law (Vienna, 1989) and was then accepted from a part of the theorist. The second part gives an overview of the most important criteria on which these divisions are based. Although also pointing to some other possible criteria, the author notes that in the end everything is mainly reduced to whether the international community precisely criminalizes, prosecutes and punishes the perpetrators, or establishes special international courts, responsible for determining the criminal responsibility of the defendants and, when there is appropriate, sentencing them. The third, most important part is a critical review. After pointing out a number of specific reasons for this, the author concludes that there is no reason to make a difference between international crimes in the wider and broader sense. He believes that various divisions of international crimes are welcome, but this one does not seem justified.